Application of on-line C30 RP-HPLC-NMR for the analysis of flavonoids from leaf extract of Maytenus aquifolium - Vilegas, Wagner [UNESP]; Vilegas, Janete H. Y.; Dachtler, Markus; Glaser, Tobias; Albert, Klaus (Wiley, 2000)
The application of on-line C30-reversed-phase high-pressure liquid chromatography-nuclear magnetic resonance spectroscopy is described for the analysis of tetraglycosylated flavonoids in aqueous and hydroalcoholic extracts of the leaves of Maytenus aquifolium (Celastraceae). Triacontyl stationary phases showed adequate separation for on-line 1H-NMR measurements at 600 MHz and allowed the characterisation of these flavonoids by detection of both aromatic and anomeric proton signals. Copyright (C) 2000 John Wiley and Sons, Ltd.
Keywords: C30-stationary phase; Flavonoids; Maytenus (celastracene); On-line HPLC-NMR; alcohol; carbon; flavonoid; plant extract; chemical analysis; controlled study; drug structure; Maytenus aquifolium; nonhuman; nuclear magnetic resonance spectroscopy; online system; plant; plant leaf; reversed phase high performance liquid chromatography; structure analysis; technique; Celastraceae; Maytenus